FAKTORFAKTOR YANG MEMENGARUHI STATUS PERFORMA PASIEN TUMOR INTRAKRANIAL DI RSUPN DR CIPTO MANGUNKUSUMO - Mariana Nur Laila,* Rini Andriani,** Henry Riyanto Sofyan,*** Tiara Aninditha*** (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION PATIENTS DIAGNOSED WITH MALIGNANCY HAVE A LONG COURSE OF ILLNESS FROM DIAGNOSIS TO TREATMENT ASSESSMENT OF PERFORMANCE STATUS PS IS ESSENTIAL TO GIVE AN OVERVIEW OF THERAPEUTIC READINESS AND PATIENTS PROGNOSIS KARNOFSKY PERFORMANCE SCALE IS A PS ASSESSMENT USED WIDELY IN NEUROONCOLOGY PATIENTS THIS INSTRUMENT CAN ASSESS FUNCTIONAL IMPAIRMENT AMONG PATIENTS TO THIS DATE CLINICAL FACTORS IN ADMISSION TIME THAT INFLUENCES KPS IN HOSPITALIZED INTRACRANIAL TUMOR HAS NOT BEEN RESEARCHED